Incidence of neurological and psychiatric comorbidity over time: a population-based cohort study in Ontario, Canada. (2nd February 2022) - Maxwell, Colleen J; Maclagan, Laura C; Harris, Daniel A; Wang, Xuesong; Guan, Jun; Marrie, Ruth Ann; Hogan, David B; Austin, Peter C; Vigod, Simone N; Swartz, Richard H; Bronskill, Susan E
Abstract: Introduction: Comprehensive, population-based investigations of the extent and temporality of associations between common neurological and psychiatric disorders are scarce. Methods: This retrospective cohort study used linked health administrative data for Ontarians aged 40–85 years on 1 April 2002, to estimate the adjusted rate of incident dementia, Parkinson's disease (PD), stroke or mood/anxiety disorder (over 14 years) according to the presence and time since diagnosis of a prior disorder. Sex differences in the cumulative incidence of a later disorder were also examined. Results: The cohort included 5, 283, 546 Ontarians (mean age 56.2 ± 12.1 years, 52% female). The rate of dementia was significantly higher for those with prior PD (adjusted hazard ratio [adjHR] 4.05, 95% confidence interval [CI] 3.99–4.11); stroke (adjHR 2.49, CI 2.47–2.52) and psychiatric disorder (adjHR 1.79, CI 1.78–1.80). The rate of PD was significantly higher for those with prior dementia (adjHR 2.23, CI 2.17–2.30) and psychiatric disorder (adjHR 1.77, CI 1.74–1.81). The rate of stroke was significantly higher among those with prior dementia (adjHR 1.56, CI 1.53–1.58). Prior dementia (adjHR 2.36, CI 2.33–2.39), PD (adjHR 1.80, CI 1.75–1.85) and stroke (adjHR 1.47, CI 1.45–1.49) were associated with a higher rate of an incident psychiatric disorder. Generally, associations were strongest in the 6 months following a prior diagnosis and demonstrated a J-shape relationship over time. Significant sex differences were evident in the absolute risks for several disorders. Conclusions: The observed nature of bidirectional associations between these neurological and psychiatric disorders indicates opportunities for earlier diagnosis and interventions to improve patient care.